Copula based polychotomous choice selectivity model: Application to occupational choice andwage determination of older workers - Wichian,A. (Springer Verlag, 2015)
© Springer International Publishing Switzerland 2015. This paper aims to estimate the occupational choice equation simultaneously with wage equation for older workers in Thailand by applying the copula approach to a polychotomous choice selectivity model. Several of the copula functions, such as the Frank and Student’s t copulas are compared to the standard model which is restricted to a joint normality assumption. This paper demonstrates that a polychotomous choice selectivity model based on the copula approach performs better than the standard one. And, it is evident that among the copula based model, the Frank copula-based model provides the best fit. Also, these results show the presence of highly significant dependency of unobservable factors between the occupational choice regression and the wage regression for unskilled and skilled workers, which implies that the selectivity bias exists. The empirical results show that the older workers who live in Bangkok earn higher wage than those who live outside Bangkok. The gender variable has no impact on wages for the high skilled older workers. For the unskilled, the male worker earns more. A surprised result is that the experience has the significantly negative impact on the wages regardless of the level of the skill of the older workers. This needs serious further research in depth to explain this phenomena.